(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Obesity and diabetes are strongly linked and increase the risk of other critical diseases such as cardiovascular disease, which is highly prevalent today. Currently available synthetic anti-diabetic drugs often cause gastrointestinal side effects, highlighting the need for alternative treatments derived from natural resources, which tend to have fewer side effects and are generally safer. The kuini fruit (Mangifera odorata) has been shown to exhibit high antioxidant activity. However, as an underutilized fruit, there is a lack of studies on its potential health benefits, particularly its antiobesity and anti-diabetic properties. Due to the high demand for rich constituents of bioactive compounds, fermentation is considered a viable method to enhance the nutritional value of this fruit. This study evaluates the potential health benefits of fermented kuini (FK) as an antiobesity and anti-diabetic agent through adipogenesis inhibition in vitro using the 3T3-L1 preadipocyte cell line, as well as its inhibition of α-amylase and α-glucosidase activities. A cell viability assay was conducted to assess the toxicity of different sample concentrations. It was found that concentrations below 1.5 mg/mL did not exhibit cytotoxicity, while higher concentrations reduced cell viability. Fermented kuini (FK) showed lower adipogenesis inhibition compared to pasteurized kuini (PK). The highest inhibition of α-amylase activity was observed at 1.0 mg/mL FK, with a percentage inhibition of 41.6%. Similarly, the highest inhibition of α-glucosidase activity was observed at the same concentration, with a percentage inhibition of 39.0%. Based on the data generated, FK demonstrates potential antiobesity and anti-diabetic properties and could serve as an alternative strategy for managing obesity and diabetes.